Evaluating the Language-in-Education Policy of 1997: Advancing inclusivity and multilingual education - Mulaudzi, Lebohang (Journal for Language Teaching, 2024)
This paper is a critical analysis of the Norms and Standards for Language Policy in Public Schools in terms of the South African Schools Act 84 of 1996. The evaluation focuses on its objectives, implementation, and impact on promoting inclusivity and linguistic diversity in education. The study was prompted by the persisting disparities in access to quality education based on linguistic backgrounds in post-apartheid South Africa. Using a conceptual framework based on theories of inclusive education, translanguaging pedagogy, and policy implementation, this study explores the policy’s objectives, scope, and how it addresses equity and access for diverse language groups. Additionally, it assesses implementation strategies and evaluates the policy’s strengths and weaknesses in promoting inclusive education and multilingualism. The article recommends establishing specific, measurable objectives and targets, formulating an action plan for consistent implementation, prioritising teacher training and support programs, and encouraging community involve-ment. By addressing these shortcomings, South Africa can advance inclusivity and multilingualism in its public schools, fostering an equitable and enriching learning environment for all learners.